Niche-specific epigenetic interventions in the spatially heterogeneous glioblastoma microenvironmental landscape: strategies for radiotherapy enhancement - Wang, Junjie; Li, Kunjie; Wang, Yongzhe; Zhang, Junyi; Peng, Xin; Ji, Ning (Frontiers in Molecular Biosciences, 2025)
Glioblastoma (GBM) remains incurable, largely due to inherent radiotherapy resistance driven by synergistic crosstalk between spatial heterogeneity and epigenetic dysregulation. Distinct tumor microenvironments—hypoxic cores, invasive edges, and perivascular regions—harbor glioblastoma-initiating cells (GICs) with unique epigenetic traits that promote radiation evasion: hypoxic cores activate the HIF–SIRT axis to maintain quiescence; invasive edges employ EZH2-mediated H3K27me3 to drive proneural–mesenchymal transition (PMT); and perivascular niches utilize HDAC–DNA repair and BRD4–super-enhancer mechanisms to sustain stemness. Concurrent epigenetic alterations—such as MGMT promoter methylation, aberrant histone modifications, and chromatin remodeling—further enhance adaptive plasticity. This review synthesizes recent preclinical and clinical evidence (2019–2024) to delineate how spatial and epigenetic mechanisms form a “resistance loop” that subverts radiotherapy. We argue that effective radiosensitization requires niche-specific strategies: HDAC inhibitors in hypoxic regions to impair DNA repair, EZH2 inhibitors at invasive margins to suppress PMT, and BET inhibitors in perivascular zones to target stemness programs. We propose a “spatial-epigenetic precision pipeline” involving: (1) mapping niche-specific epigenetic signatures via spatial multi-omics; (2) developing ligand-functionalized nanocarriers for targeted delivery; and (3) designing adaptive combinatory regimens (epigenetic agents with radiotherapy and immunotherapy) based on dynamic response monitoring. This framework aims to disrupt spatial–epigenetic crosstalk, potentially transforming GBM into a chronically manageable disease.